Pengaruh Penggunaan Animasi pada Mata Pelajaran IPAS Terhadap Hasil Belajar Siswa Kelas V SD Negeri 08 Kampung Batu Dalam Kabupaten Solok - Handayani, Elsa; Zuliarni, Zuliarni; Hidayati, Abna; Eldarni, Eldarni; Rahmi, Ulfia (Indo-MathEdu Intellectuals Journal, 2024)
The main problem is the low learning outcomes of students, which is caused by the lack of variety in teaching methods and the lack of use of digital media. This study aims to determine the influence of the use of animation as a learning medium for science and technology on the learning outcomes of grade V students at SD Negeri 08 Kampung Batu Dalam. The study used a quasi-experimental method with a posttest only control group design, involving students in grades V.a and V.b, each totaling 21 people. The data collection technique uses tests. Analysis of test result data using t-test. The results of the analysis showed that students who learned using animation obtained a higher average score (70.71) compared to students who used traditional methods (55.48). This proves that animation is effective in improving students' understanding and learning outcomes on human circulatory system materials that are abstract and require visualization